A multi-modal delivery strategy for spinal cord regeneration using a composite hydrogel presenting biophysical and biochemical cues synergistically. (September 2021) - Man, Weitao; Yang, Shuhui; Cao, Zheng; Lu, Jiaju; Kong, Xiangdong; Sun, Xiaodan; Zhao, Lingyun; Guo, Yi; Yao, Shenglian; Wang, Guihuai; Wang, Xiumei
Abstract: Extensive tissue engineering studies have supported the enhanced spinal cord regeneration by implantable scaffolds loaded with bioactive cues. However, scaffolds with single-cue delivery showed unsatisfactory effects, most likely due to the complex nature of hostile niches in the lesion area. In this regard, strategies of multi-modal delivery of multiple heterogeneous cell-regulatory cues are unmet needs for enhancing spinal cord repair, which requires a thorough understanding of the regenerative niche associated with spinal cord injury. Here, by combining hierarchically aligned fibrin hydrogel (AFG) and functionalized self-assembling peptides (fSAP), a novel multifunctional nanofiber composite hydrogel AFG/fSAP characterized with interpenetrating network is designed. Serving as a source of both biophysical and biochemical cues, AFG/fSAP can facilitate spinal cord regeneration via guiding regenerated tissues, accelerating axonal regrowth and remyelination, and promoting angiogenesis. Giving the synergistic effect of multiple cues, AFG/fSAP implantation contributes to anatomical, electrophysiological, and motor functional restorations in rats with spinal cord hemisection. This study provides a novel multi-modal approach for regeneration in central nervous system, which has potentials for clinical practice of spinal cord injury.